Natural Radioactivity Levels and Radiation Hazards in Shore Soil and Sediments along the Coast of Ndokwa East, Delta State, Nigeria - , C. P. Ononugbo, I. Ofuonye (Archives of Current Research International, 2017)
Life on earth has developed under permanent exposure to radiation. Humans have no senses for ionizing radiation, therefore possible risks related to ionizing radiation were underestimated. The objectives of this study therefore is to measure the activity concentration of natural radionuclides in shore soil and sediment samples and determine the radiological health risk associated with exposure to them. The activity concentration of Natural Occurring Radioactive Materials (NORMs) in shore soil and sediments along the coast of Ndokwa East, Delta state were analyzed using a NaI(TI) gamma ray spectrometric technique. The total average activity concentrations of radionuclides 238U, 232Th and 40K were 140.79±18.3, 36.88±2.10 and 621.25±46.21 Bqkg-1 respectively in shore soil samples and 189.62±2.54, 53.47±1.21 and 725.62±21.03 Bqkg-1 respectively in shore sediment samples. Correlations made among these radionuclides prove the existence of secular equilibrium in the investigated shore soil. The absorbed dose rate calculated in soil and sediments were found to be twice the average safe value. The radiological health hazards such as gonads dose, excess lifetime cancer risk, internal and external hazard indices, activity utilization and gamma representative indices calculated were higher than their respective safe values. Multivariate statistical analyses (Pearson correlation, cluster and factor analysis) were carried out between the parameters obtained from radioactivity concentration to know the existing relations.